Relevant aspects for successful cementation of fiberglass posts - Zavanelli, A. C. [UNESP]; Falcón-Antenucci, R. M.; Dos Santos Neto, O. M.; Zavanelli, R. A.; Mazaro, J. V.Q. [UNESP] (My University, 2022)
The longevity of indirect restorative treatment in teeth with endodontic treatment depends on several factors. A very important factor is the cementation of the intraradicular retainer.The aim of this study was the relevant aspects for clinical success in the adhesive cementation of fiber posts. The following topics were developed: fiber post material, surface treatments, irrigation solutions used for root canal cleaning, and adhesive systems. A bibliographic search of the last 5 years was carried out, in Portuguese and English, using the databases: PubMed and Bireme. From the total of articles obtained, articles with direct link to the topic were selected, resulting in 40 scientific publications. It was concluded that: the application of silane and thermal silanization increases the bond strength between the fiber bolt and the cementing agent. The 2.5% sodium hypochlorite did not interfere with the bond strength of the fiber bolts when the total acid technique is used in conjunction with dual-set resinous cement. Self-etching adhesives have shown promise, especially when combined with self-curing cements.
Aspectos relevantes para el éxito en la cementación de los pernos fibra de vidrio
Keywords: cementation; dental bonding; post and core technique